(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article the results of scientific integrated in area of sociology, philosophy and pedagogies with the purpose of exposure of organizational and elemental mechanisms of changes of modern communicative society. Demonstrated, that informatization of society at the level of man in today’s scales becomes a factor, increasing entropy processes in society. Poved, that pedagogies comes forward the lead them in adjusting of entropy processes and conception of project sociality-cultural form of personality form which can become one of priority directions of pedagogical practice at the beginning of 21th to the in Ukraine is offered.